Inkjet Printing of Latex‐Based High‐Energy Microcapacitors. (3rd June 2019) - Torres‐Canas, Fernando; Yuan, Jinkai; Ly, Isabelle; Neri, Wilfrid; Colin, Annie; Poulin, Philippe
Abstract: Microenergy storage devices are appealing and highly demanded for diverse miniaturized electronic devices, ranging from microelectromechanical system, robotics, to sensing microsystems and wearable electronics. However, making high‐energy microcapacitors with currently available printing technologies remains challenging. Herein, the possibility to use latex polyvinylidene fluoride (PVDF) as aqueous ink for making dielectric capacitors at the microscale is shown. The dielectric properties of printed microcapacitors can be optimized based on a novel approach, i.e., mixing PVDF latex with polyvinyl alcohol (PVA) to realize dielectric organic nanocomposites. The PVA prevents the coalescence of PVDF nanoparticles and serves as a continuous matrix phase with high dielectric breakdown strength. While the well‐dispersed PVDF nanoparticles serve as highly polarizable and isolated domains, providing large electric displacement under high fields. Consequently, a high discharged energy density of 12 J cm −3 is achieved at 550 MV m −1 . These printed microcapacitors demonstrate mechanical robustness and dielectric stability over time. Abstract : A flexible and fully inkjet‐printed high‐energy microcapacitor based on aqueous dielectric inks composed of polyvinylidene fluoride (PVDF) latex and polyvinyl alcohol (PVA) binders is demonstrated. This approach uniquely combines the high breakdown strength of PVA and high polarization of PVDF, making the printed microcapacitors promising for demanding printed electronics that require microscale peak powers.